Determination of the detection limit using the four-parameter logistic model for the double-antibody sandwich ELISA for the rapid detection of Bacillus cereus in food - Masdor, Noor Azlina (Journal of Environmental Microbiology and Toxicology, 2017)
Bacillus cereus is increasingly recognized as one of the major causes of food poisoning in the industrialized world. In a previous publication, a sandwich ELISA is developed for the detection of B. cereus whole cells. The curve showed a sigmoidal calibration curve, but the model used was linear. This study remodels the sigmoidal data obtained using a four-parameter logistic (4PL) equation that can cover the whole range of data obtained. The sigmoidal ELISA calibration curve was efficiently fit by the 4-PL equation. A good correlation coefficient value of 0.996 was obtained indicating good fitting. The LOD value was 5.36 x104 CFU/mL with the 95% confidence interval from 1.07x104 to 9.64x104 CFU/mL, which is about one order of magnitude less sensitive that the previously claimed LOD. The modelling exercise shows that the 4PL equation can fit the ELISA curve very well.